2011
DOI: 10.1007/s00436-011-2306-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening for feeding deterrent activity of herbal extracts against the larvae of malaria vector Anopheles subpictus Grassi

Abstract: This no-choice, laboratory study focuses on the feeding of homogeneous powdered, dried, yeast with different plant extracts on mosquito fourth-instar larvae to determine the effects on their mortality. Screening for antifeedant activity of plant extracts with some known medicinal attributes could lead to the discovery of new agents for vector control. The aim of this study was to investigate the antifeedant activity of crude leaf hexane, ethyl acetate, acetone, and methanol extracts of Andrographis lineata Wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Crude extract of leaves or bark of the plants have been tested earlier by several investigators and larvicdal activities have been shown against C. quinquefasciatus [17][18][19][20][21][22][23].The leaf of O. gratissimum show more effective repellents activity against the C. quinquefasciatus which is in accordance with the Rajkumar's findings [24]. The methanol extracts shows 100% larval mortality at concentration of 500 ug/mL against C.quinquefasciatus is also in accordance with Rajkumar's finding [20].…”
Section: Resultsmentioning
confidence: 99%
“…Crude extract of leaves or bark of the plants have been tested earlier by several investigators and larvicdal activities have been shown against C. quinquefasciatus [17][18][19][20][21][22][23].The leaf of O. gratissimum show more effective repellents activity against the C. quinquefasciatus which is in accordance with the Rajkumar's findings [24]. The methanol extracts shows 100% larval mortality at concentration of 500 ug/mL against C.quinquefasciatus is also in accordance with Rajkumar's finding [20].…”
Section: Resultsmentioning
confidence: 99%
“…Understanding how Plasmodium - Anopheles interactions contribute to the mosquito vector competence has received great attention lately, and the increasing knowledge promises to contribute to the development of new malaria control strategies [1][3]. Malaria still remains a serious health problem in developing African countries, causing more than 1 million deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…The petroleum ether extracts of Jatropha curcas, Pedilanthus tithymaloides, Phyllanthus amarus, Euphorbia hirta and Euphorbia tirucalli exhibited LC 50 values of 11.34, 76.61, 113.40, 424.94 and 5.52 ppm, respectively, against C. quinquefasciatus (Rahuman et al 2008b). The plant extracts exhibited a significant antifeedant activity after 24 and 48 h of exposure; however, the highest larval mortality was found in ethyl acetate extracts of leaves of Anisomeles malabarica, acetone =6.40, 8.06, 7.45, 6.98 and 6.20 mg/mL), respectively, and the hexane extract of A. lineata and D. metal; methanol extract of Aristolochia bracteolata and E. prostrata showed larval mortality after 48 h (LC 50 =3.05, 2.11, 3.00 and 2.18 mg/mL; LC 90 =9.06, 6.22, 8.23 and 5.77 mg/mL), respectively, against fourth-instar larvae of A. subpictus (Elango et al 2011b). The highest adulticidal activity was observed in ethyl acetate extract of A. lineata, chloroform extract of Andrographis paniculata, acetone extract of Cocculus hirsutus and methanol extract of Tagetes erecta (LD 50 =126.92,95.82,109.40 and 89.83 ppm;LD 90 = 542.95,720.82,459.03 and 607.85 ppm).…”
Section: Discussionmentioning
confidence: 99%